2021
DOI: 10.1002/cae.22425
|View full text |Cite
|
Sign up to set email alerts
|

Using peer code review to improve computational thinking in a blended learning environment: A randomized control trial

Abstract: Although the importance of computational thinking (CT) has been widely recognized, we still poorly understand how to effectively teach this skill. The aim of this study is to investigate whether peer code review (PCR) could affect CT, learning engagement, and learning satisfaction in a blended learning environment. To achieve this, we carried out a randomized control trial study involving 84 first-year undergraduates (second semester) from different majors. There was no difference in CT before this experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The results suggested that behavioral engagement needed not to be considered when improving students' algorithmic thinking. Thus, instructors focused on providing various programming tasks, guidance [30], and emotional support [40] during classroom activities to improve students' emotional and cognitive engagement. However, the influence of emotional and cognitive engagement on creativity varied in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that behavioral engagement needed not to be considered when improving students' algorithmic thinking. Thus, instructors focused on providing various programming tasks, guidance [30], and emotional support [40] during classroom activities to improve students' emotional and cognitive engagement. However, the influence of emotional and cognitive engagement on creativity varied in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…It includes 29 items, which are distributed into five subscales. This widely‐used scale is a general CT evaluation method (Kilic et al, 2021; Lin et al, 2021). We performed a back‐to‐back translation whereby experts in both Chinese and English helped check the language's accuracy and coherence.…”
Section: Methodsmentioning
confidence: 99%
“…evaluation method (Kilic et al, 2021;Lin et al, 2021). We performed a back-to-back translation whereby experts in both Chinese and English helped check the language's accuracy and coherence.…”
Section: Instrumentsmentioning
confidence: 99%